Fuzzified Single Phase Automatic Sequential Reactive Power Compensation with Minimized Switches - K. Shashikumar; C. Venkataseshaiah; K. S. Sim (Universitas Ahmad Dahlan, 2018)
The current rapid growth in IoT technology facilitates the effortless implementation of bidirectional remote monitoring and control system implementation in homes and buildings. We have modeled an actual non-intrusive PnP sequential SVC prototype hardware and wireless FLC automation software design on a real single phase home appliances system as load modeling. In addition, we have also designed a novel Unidirectional MOSFET Switched Capasitor model (UniMosSC) which enables us to reduce the hardware cost and increase the life span of SVC due it uses minimum switching devices. The system we have designed is able to correct the power factor at the root of the problem at each appliance. Due to complexity of appliance clustering and overlapping clusters, we implemented fuzziness in the system for more reliability in computations. The system could be used in homes or buildings resulting in electricity bill reduction, saving dollars and cents.